Analisis Faktor-Faktor yang Memengaruhi Kelancaran Pengembalian Pembiayaan Murabahah pada Usaha Mikro, Kecil, dan Menengah (UMKM) di BMT Taruna Sejahtera - Rahayu, Tri Andina (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
A problem arising from the distribution of defrayal is often caused by a delay in repayment of financing that could interfere in liquidity and profitability of financial institution. One of BMTs that has good achievement in Semarang is BMT Taruna Sejahtera with a percentage of the value of arrears of the last few years has decreased. This achievement needs to be maintained and improved until the problems can be solved. This research was conducted at BMT Taruna Sejahtera starting from February to August 2014 using a purposive sample of 85 debtors. All the factors which are supposed to influence the rate of return on the financing were analyzed using multiple linear regression analysis. As the response variable in the analysis, that is the level of the smoothness in returning defrayal (Y) in which the predictor variables are the personal characteristics consisting of the level of education and age. Based on the results of multiple linear regression analysis, the factors that affect the rate of return is the value of the loan financing, business turnover, and level of education. It means the higher the value of the loan, the business turnover and debtor’s education level, the greater the chances of returning of murabaha defrayal